PENERAPAN UNSUR MONUMENTAL DALAM PENDAMPINGAN RENOVASI TERAS MASJID AHMAD HIDAYAH DI KOTA BANDUNG - Wiyoso, Aghastya; Nikolay, Francis; Kalyani, Khema Dwi (Jurnal Serina Abdimas, 2023)
ABSTRACT The existence of a mosque that accommodates ritual worship and social activities of its congregation needs always to be appreciative of the needs of its congregation. For mosque facilities that have been present in the community, the sustainability of facility services is important, as well as the continuity of physical performance and visual expression that always needs to be representative. Ahmad Hidayah Mosque in Bandung City also showed its aspirational attitude towards this need, by carrying out renovation activities on the terrace which is the face and identity marker of the mosque. In particular, the technical problem of renovation is the asynchronicity between the old and new buildings that need to be harmonized and the absence of accessibility orientation on the façade. These two technical problems led to the initiation of a monumental design approach; The most responsive approach to the demands of fulfilling the aesthetic, technical, functional, and psychological values of solving these two problems. At the same time, this renovation activity plan faces obstacles in the form of limited human resource competencies faced by mosque administrators and needs to be solved. This problem became the background for implementing community service activities from the Interior Design team, Untar by involving the management of the Mosque Prosperity Council as partners and the renovation committee and internal mosque workers as the target of activities. The method implemented in the activity is in the form of technical assistance in a collaborative-participatory paradigm for the scope of design and implementation of renovation work, including redesigning the terrace & front hall area and several supporting spaces in this area. ABSTRAK Keberadaan masjid yang mengakomodasi peribadatan ritual dan kegiatan sosial jemaahnya perlu senantiasa apresiatif terhadap kebutuhan jemaahnya. Untuk sarana masjid yang telah hadir di tengah masyarakat, keberlanjutan layanan fasilitasnya menjadi penting, demikian juga dengan kontinuitas performa fisik dan ekspresi visualnya yang senantiasa perlu representatif. Masjid Ahmad Hidayah di Kota Bandung juga memperlihatkan sikap aspiratifnya terhadap kebutuhan tersebut, dengan melakukan kegiatan renovasi pada bagian teras yang merupakan perwajahan dan penanda identitas masjid. Permasalahan teknis renovasi secara khusus adalah adanya asinkronitas antara bangunan lama dan baru yang perlu diselaraskan dan ketiadaan orientasi aksesiblitas pada fasad. Dua permasalahan teknis tadi mencetuskan inisiasi pendekatan desain monumental; pendekatan yang paling responsif terhadap tuntutan pemenuhan nilai estetik renovasi, teknis fungsional sekaligus psikologis dari pemecahan dua masalah tersebut. Pada saat yang sama rencana kegiatan renovasi ini menghadapi kendala berupa keterbatasan kompetensi sumber daya manusia yang dihadapi pengurus masjid dan perlu dipecahkan. Permasalahan tersebut menjadi latar belakang dilakukannya kegiatan pengabdian kepada masyarakat dari tim Desain Interior, Untar dengan melibatkan pengurus Dewan Kemakmuran Masjid sebagai mitra dan panitia renovasi serta pekerja internal masjid sebagai sasaran kegiatan. Metoda yang dilaksanakan dalam kegiatan berupa pendampingan teknis dalam paradigma kolaboratif-partisipatif untuk lingkup perancangan dan pelaksanaan dari pekerjaan renovasi yang meliputi redesain area teras & selasar muka, serta beberapa ruang pendukung pada area ini.